2020
DOI: 10.1002/er.5371
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient surface modified separator fabricated with atmospheric atomic layer deposition for high temperature lithium ion batteries

Abstract: Summary A high throughput mass production of separator is proposed using a well‐established unique in‐house process of roll‐to‐roll atmospheric atomic layer deposition. An ultra‐thin conformal layer of Al2O3 is deposited over the commercial Celgard (PE/PP/PE) using multi‐slit gas source head. Overall 10 nm increase is incurred in the thickness, while maintaining the porosity to ~48%. The entire process of fabrication was performed at very low temperature of 90°C. The high thermal stability of as‐modified separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Moreover, by introducing the colloidal La 2 O 3 nanocrystals in PVDF‐HFP matrix also suppresses the strong vibrations bands between 400 and 800 cm −1 related to α and β crystalline phases in PVDF‐HFP 47‐50 . The reduction in peaks corresponding to α and β crystalline phases assures the more amorphous nature of composite separator which helps to improve the electrolyte uptake and further improvement in ionic conductivity 51‐53 . The strain‐stress curves of commercial, PVDF‐HFP and proposed separators are given in Figure 2D.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, by introducing the colloidal La 2 O 3 nanocrystals in PVDF‐HFP matrix also suppresses the strong vibrations bands between 400 and 800 cm −1 related to α and β crystalline phases in PVDF‐HFP 47‐50 . The reduction in peaks corresponding to α and β crystalline phases assures the more amorphous nature of composite separator which helps to improve the electrolyte uptake and further improvement in ionic conductivity 51‐53 . The strain‐stress curves of commercial, PVDF‐HFP and proposed separators are given in Figure 2D.…”
Section: Resultsmentioning
confidence: 99%
“…reported a multilayer separator with an ultrathin 5 nm Al 2 O 3 layer through a novel roll‐to‐roll atmospheric ALD technology, which showed excellent flexibility, high conformity, suppressed thermal shrinkage, high electrolyte wettability, and improved tensile strength. [ 15 ] Despite these advantages, the relatively low productivity and high cost, as compared to ceramic‐coated separators, may limit its commercial application.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al reported a multilayer separator with an ultrathin 5 nm Al 2 O 3 layer through a novel roll-to-roll atmospheric ALD technology, which showed excellent flexibility, high conformity, suppressed thermal shrinkage, high electrolyte wettability, and improved tensile strength. [15] Despite these advantages, the relatively low productivity and high cost, as compared to ceramic-coated separators, may limit its commercial application. Herein, our high thermal stability CCS@PFR separator, which was prepared by further modifying single-side ceramiccoated separator with a 3D PFR-coated layer throughout the entire separator, was chosen as a substrate separator.…”
Section: Thermal Dimensional Stability Of App-modified Separatormentioning
confidence: 99%
“…Over the past few years, flexible electronics has significantly captured researchers' attention owing to its myriad applications, including physiological monitoring, (1)(2)(3) wearable electronics, (4)(5)(6) medical devices, protheses, smart clothes, and soft robotics. (7)(8)(9) In flexible devices, soft strain sensors play a major role owing to their vibrant features, such as high compliance, low weight, long lifetime, low cost, and the ability to sense the complex movements of soft robots and human body parts. (10) Unlike conventional sensors with rigid electronic subsystems and a limited sensing range, the robust design structure of soft sensors makes them ideal as an integral part of such high-end feedback applications.…”
Section: Introductionmentioning
confidence: 99%